PENGARUH DOSIS Beauveria bassiana DAN PESTISIDA NABATI(Mimba) TERHADAP PERSENTASE SERANGAN HAMA PENGGEREKBUAH KOPI (Hypothenemus hampei) - HARYUNI HARYUNI; WIYONO WIYONO; SRI HANDOYO (JURNAL ILMIAH AGRINECA, 2017)
The research to find out the effect of Beauveria bassiana dose, organicpesticide dose and interaction of Beauveria bassiana with organic pesticide onthe percentage pest attack of berries borer coffee. This study was conducted inCoffee Garden in Kalibening Village of Kebondalem Village of Jambu SubDistrict of Semarang Regency. By using a factorial completely random groupdesign method with two factors. The first factor was the dose of Beauveriabassiana organic controlling agent (A), administration consisting of : A0 =without treatment; A1 = 1 kg/Ha; A2 = 2 kg/Ha; A3 = 3 kg/Ha. The second factorwas the dose of organic pesticide (T) administration consisting of : T1 = 100ml/Ha; T2 = 200 ml/Ha; T3 = 300 ml/Ha. The result showed that the interaction ofBeauveria bassiana dose and organic pesticide dose treatments affectedsignificantly, the lowest percentage of attack occurred in the combination of A3T2treatment as 0,38 % with the Beauveria bassiana dose of 3 kg/ha and the organicpesticide dose of 200 ml/Ha.